Evolution of INDITEX group’s internationalization strategy in Latin America - Benavides, Giovanny Fernando (Cuadernos de Administración, 2024)
In 2022, the INDITEX Group experienced a 12% increase in sales compared to the previous year, driven by its sustainability strategy, new product development, and integrated platforms. This growth was seen in both physical stores and online. Additionally, international expansion over the last decade, particularly in Latin America and Asia, contributed to these positive results. This manuscript analyzes the internationalization strategies applied in INDITEX’s sustained expansion, focusing on the group’s global positioning in various areas such as competition, business development, logistics, and offshoring strategies. It aims to investigate the maneuvers undertaken over the years, with a particular focus on Latin America—a region characterized by its unique country-specific instabilities and market demand variations. To achieve this, an exploratory-descriptive methodology will be employed, consisting of four steps: first, an exploratory descriptive phase will expand the bibliographic material with an emphasis on official company reports and specialized fashion and marketing magazines; second, an analytical description through a comprehensive and selective report will identify the investigated criteria; third, an exploratory-analytical phase will group and analyze the elements related to the studied topic; and fourth, a comparative analysis will seek direct or indirect correlations between internationalization strategies and brand growth.